Organizational Maintenance, Sensitivity to Clients, and Vulnerability The Villain as Ambiguous Hero. Discussion Paper #442-77 - Sosin, Michael; Wisconsin Univ., Madison. Inst. for Research on Poverty ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1977)
This paper reexamines the concept of organizational maintenance and argues that the common assumption of an inverse relation between maintenance and the sensitivity of organizations to client needs is not valid. A logical analysis suggests that maintenance should lead to a greater sensitivity to environmental forces that control important resources; if these forces are in the direction of supporting sensitivity to clients, organizations with a maintenance orientation will be more sensitive. The idea that maintenance (defined and operationalized as an orientation toward maintaining comfortable working conditions) relates to attempts to develop ties with environmental forces, and further, that there is a positive relation between maintenance and client sensitivity that is mandated by law is demonstrated using a national sample of juvenile courts. This relation is especially strong when the juvenile courts are vulnerable to legal pressure. Moreover, maintenance has varying relations to other reactions to clients, depending on the relation between the court and the environment. It is concluded that a maintenance orientation is often consistent with sensitivity to clients and might even be used to increase sensitivity. (Author)
Sponsoring Agency: Department of Health, Education, and Welfare, Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Court Litigation; Due Process; Juvenile Courts; Organization; Organizational Development; Organizational Effectiveness; Organizational Theories; Professional Services; Statistical Analysis; Tables (Data); Work Environment; Reports, Research